Optimal design of laminated-MRE bearings with multi-scale model. (26th September 2016) - Chen, Shiwei; Wang, Xiaojie; Zhang, Ze; Mu, Wenjun; Li, Rui
Abstract: In the design of a laminated magneto-rheological elastomeric bearing (MREB), the passive rubbers are replaced with composite layers of rubber and MREs. The applied magnetic field, produced by the built-in electromagnet through the input current, changes the stiffness and damping of MREs, and thus that of the device. Typically, a good MREB should possess higher adjustable properties with less activating power in avoiding overheating problem. Thus an optimized design of MREB should integrate the MRE material design into mechanical and electromagnetic components to achieve a trade-off between power consumption and adjustability of stiffness. In this study, we propose a method to analyze and design a laminated MRE bearing, in which the optimal parameters of materials and mechanical structure of the MRE bearing are determined. Based on the multi-scale and magneto-mechanical coupling theories, we establish a multi-scale model for the MRE bearing considering the influence of particle volume fraction, particle distribution, and thickness of MRE laminated layers on its mechanical performance. Within the micro-scale analysis, the representative volume unit is used to address the effect of particle volume fraction and distribution on mechanical and magnetic properties of MRE itself. Within the macro-scale analysis, we build both mechanical and magnetic models for the laminated MRE bearing. Based on the theoretical analysis, a laminated MRE bearing with four-layer MRE is designed and fabricated. The performance of the MRE bearing has been tested by using MTS test bench. The results are compared with that of model analysis. Both experimental and theoretical results indicate that optimal design of MREB depends on the MRE's particle volume fraction which is related with MREB's input power limitation.